03.12 Tnfr2+regulatory t cells subpopulations are highly suppressive and are increased on anti-tnf treatment. (1st March 2017) - Santinon, François; Batignes, Maxime; Pouchy, Charlotte; Salomon, Benoit; Decker, Patrice; Boissier, Marie-Christophe; Semerano, Luca; Bessis, Natacha
Abstract : Background: In rheumatoid arthritis (RA), regulatory T cells (Tregs) are defective in their suppressive capacities and fail to control chronic inflammation. TNF-α is involved in inhibition of Treg differentiation and activation, likely via activation of TNF type 1 receptor (TNFR1). 1 Conversely, activation of TNFR2 on Tregs is critical for their phenotypic and functional stability in the inflammatory environment. 2 Moreover, it has been shown that therapeutic TNF blockade with the anti-TNF monoclonal antibody adalimumab restores the potency of Treg cell suppression in RA by binding to membrane TNF- α on monocytes and promoting Treg cell expansion through enhanced TNFR2 signaling. 3 In the present study we aimed to establish the role of TNFR2 on Tregs in control of inflammation at multiple levels, by: 1) studying the action of TNF on Treg function in the presence and absence of TNFR2 in vitro, 2) testing the severity of a model of skin inflammation in TNFR2KO mice, 3) evaluating the evolution of TNFR2-expressing Treg from RA patients during anti-TNF treatment. Materials and methods: Mice deficient in the TNFR2 gene (TNFR2 KO) and TNFR2 lox/lox mice to conditionally delete TNFR2 specifically in Tregs were used. CD4 + CD25 + Treg cells were purified by magnetic sorting. Cell phenotype was evaluated by flow cytometry. ATP concentrations were determined by luminometry. Skin inflammation was induced by applying an imiquimod-containing ointment, to the skin. Peripheral blood Treg where characterised before and after 3 months of anti–TNF treatment in 10 RA patients. Results: In vitro, TNF-α enhanced Foxp3 maintenance through TNFR2 signalling in cultured Tregs. In vivo, TNFR2-negative Treg cells, from both TNFR2KO and TNFR2 lox/lox mice, had lower spontaneous suppressive capacities (lower ATP hydrolysis, inhibition of effector T cells proliferation and IFN-γ production). Compared to wt mice, TNFR2KO mice had enhanced skin-inflammation and decreased Treg frequency in lymph nodes. In RA patients, TNF blockade induced an increase in the frequency of TNFR2-expressing Tregs at 3 months of treatment vs. the baseline Conclusions: TNFR2 signalling on Tregs may play a major role in controlling inflammation and can be activated both by TNF-α and anti-TNF treatment. Further studies to dissect TNFR2 dependent pathways on Tregs are warranted. References: Nie H, Zheng Y, Li R, et al. Phosphorylation of FOXP3 controls regulatory T cell function and is inhibited by TNF-α in rheumatoid arthritis. Nat Med2013;19:322-8. Chen X, Wu X, Zhou Q, et al. TNFR2 is critical for the stabilisation of the CD4+Foxp3+ regulatory T cell phenotype in the inflammatory environment. J Immunol. 2013;190:1076-84. Nguyen DX, Ehrenstein MR. Anti-TNF drives regulatory T cell expansion by paradoxically promoting membrane TNF-TNF-RII binding in rheumatoid arthritis. J Exp Med2016;213:1241-53.